PENGARUH FASILITAS DAN HARGA TERHADAP LOYALITAS KONSUMEN PADA AKBAR FUTSAL SITUBONDO DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING - Sukron, Muhammad; Tulhusnah, Lusiana; Pramesthi, Riska Ayu (Fakultas Ekonomi dan Bisnis, 2023)
Marketing is an important element in a company to determine the success or failure of a business, for this reason the company must apply the notion of marketing to a large extent in order to survive. The purpose of this study is to determine the effect of facilities and prices on consumer satisfaction. The population in this study are all consumers who come to Akbar Futsal Situbondo. Random sampling method (simple probability sampling) regardless of strata in the population in this study. In taking this sample using a presentation level of 10%. Data analysis and hypothesis testing in this study used the Least Squere Partial Structural Equation Model (PLS-SEM). The results of the hypothesis test have a direct effect using the smart PLS 3.0 application, indicating that facilities and prices have a significant positive effect on consumer satisfaction, facilities have a significant positive effect on consumer loyalty, prices have a positive but not significant effect on consumer loyalty, satisfaction has a significant positive effect on consumer loyalty, facilities and Price has a significant positive effect on consumer loyalty through consumer satisfaction.